MENEMBUS PASAR UMKM: STRATEGI JITU PENGEMBANGAN PEMASARAN DAN BISNIS - Aditiya, Variza; Lastri, Novelma; Musdiana, Andi Desy; Hartutik, Dwi; Mustafa, Said (Smart Education, 2025)
Abstract: This research is a literature review aimed at analyzing marketing and business development strategies through three case studies: Warung Makan Asyik in Balunijuk Village, the skincare product Cozy Cosmetic, and the Nasi Gigit Candu business network. These three studies demonstrate different yet complementary approaches to designing and implementing marketing strategies to increase competitiveness and sales. Through a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, this research identifies internal and external factors influencing the success of each business. The results indicate that leveraging product uniqueness, adapting to market trends, and optimizing social media are crucial elements of an effective marketing strategy. Furthermore, collaboration, product innovation, and appropriate market segmentation are also key drivers of sustainable business development. This literature review is expected to provide theoretical and practical contributions to micro, small, and medium enterprises (MSMEs) in designing marketing development strategies relevant to current market conditions.Keywords: Marketing Strategy, Business Development, SWOT Analysis, MSMEs, Marketing Literacy Abstrak: Penelitian ini merupakan literatur review yang bertujuan untuk menganalisis strategi pengembangan pemasaran dan bisnis melalui studi terhadap tiga kasus: Warung Makan Asyik di Desa Balunijuk, produk skincare Cozy Cosmetic, dan jaringan bisnis Nasi Gigit Candu. Ketiga studi tersebut menunjukkan pendekatan yang berbeda namun saling melengkapi dalam merancang dan menerapkan strategi pemasaran guna meningkatkan daya saing dan penjualan. Melalui analisis SWOT (Strengths, Weaknesses, Opportunities, Threats), penelitian ini mengidentifikasi faktor internal dan eksternal yang mempengaruhi keberhasilan masing-masing bisnis. Hasil kajian menunjukkan bahwa pemanfaatan keunikan produk, adaptasi terhadap tren pasar, dan optimalisasi media sosial menjadi elemen penting dalam strategi pemasaran yang efektif. Selain itu, kolaborasi, inovasi produk, dan segmentasi pasar yang tepat juga menjadi pendorong utama dalam pengembangan bisnis yang berkelanjutan. Literatur review ini diharapkan dapat memberikan kontribusi teoritis dan praktis bagi pelaku usaha mikro, kecil, dan menengah (UMKM) dalam merancang strategi pengembangan pemasaran yang relevan dengan kondisi pasar saat ini.Kata kunci: Strategi Pemasaran, Pengembangan Bisnis, Analisis SWOT, UMKM, Literasi Pemasaran